TIPOLOGI DAN SEBAB-SEBAB POST CONFLICT VIOLENCE DI ACEH (2005-2012) - , Shary Charlotte Henriette Pattipeilhy ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Objective of the research entitled âTypology and Causes of Post Conflict Violence in Aceh (2005-2012)â is to explain the characteristics and causes of post conflict violence in Aceh. Eventhough the separatist violence in Aceh has ended in 2005, but violent conflict in Aceh continues to increase and is often concentrated in the pre MoU conflict area. The term post-conflict can trap us into a common perception that the conflict has ended and replaced by peace, or to equate "conflict" to "war" and "post- conflict" to "peaceâ. In post-conflict situations, the intensity of the conflict is much reduced